Observations on livestock productivity in sheep fed exclusively on haulms from ten different genotypes of groundnut - Prasad, Kodukula V.S.V.; Khan, A.A.; Vellaikumar, S.; Devulapalli, R.; Ramakrishna Reddy, C.; Nigam, S.N.; Blümmel, Michael (2010)
Haulms from 10 different genotypes of groundnut were tested with growing male sheep for digestibility, intake, nitrogen retention and live weight gains. Very high daily intake levels of > 4% of sheep bodyweight were observed in all haulms. Nitrogen retention (range: 6.7 to 11.4 g/d) and live weight gains (range: 65 to 137 g/d) varied about two fold among genotypes suggesting that the choice of groundnut genotype can have a very significant effect on livestock productivity in feeding systems based on groundnut haulms. Haulm fodder quality difference were well reflected by acid detergent lignin (ADL), which accounted for 58, 39 and 72% of the variation in haulm in vivo digestibility, nitrogen retention and live weight gains, respectively. Using stepwise multiple regression procedures, combinations of haulm ADL content and in vitro digestibility and of haulm ADL content and in vitro metabolisable energy content accounted for 84% and 92% of the variation in in vivo digestibility and live weight gain, respectively. The combination of haulm nitrogen and ADL content accounted for 80% of the variation in nitrogen retention. Among the genotypes, ICGV 89104), ICGV 91114), TMV 2 and ICGV 92093 promoted highest productivity in sheep.